A randomized phase II trial of MOVING ON: An intervention to increase exercise outcome expectations among breast cancer survivors. Issue 10 (11th September 2018) - Hirschey, Rachel; Kimmick, Gretchen; Hockenberry, Marilyn; Shaw, Ryan; Pan, Wei; Page, Christina; Lipkus, Isaac
Abstract: Objective: The objective of the study is to test theoretical intervention fidelity and feasibility of MOVING ON, a self‐directed, home‐based, randomized controlled trial to increase exercise outcome expectations (OEs) (what one expects to obtain or avoid as a result of a behavior or lack thereof), among breast cancer survivors. Method: Stage Ia to IIb survivors (n = 60) were given the MOVING ON intervention or control booklet. Data were collected through online surveys and an accelerometer at baseline, 4, 8, and 12 weeks postintervention. Fidelity was measured by questions assessing participant perceptions of MOVING ON (score ≥2) and direction of intervention effects. Feasibility was measured by recruitment rate (target of 60 participants in 6 months), retention (total attrition <17%), and acquisition of accelerometer data (% ≥subjective exercise data obtained). Analyses consisted of descriptive statistics, mixed models, and content analysis. Results: Fidelity met a priori criteria (mean = 3.31, SD = 0.87). Outcome expectations increased 0.01 points, and weekly steps increased by 970 every 4 weeks in the intervention arm compared to the control arm. All effect sizes were small, ranging from 0.01 to 0.09. Target enrollment, achieved in 17 weeks, met a priori feasibility criteria. Retention (66%) and accelerometer data acquisition (60%) (compared to 73% of subjective exercise data) did not. Conclusion: MOVING ON influenced OEs as intended and was well received by participants. A fully powered study, of this low‐cost, easy‐to‐implement intervention, is warranted. Intervention and measurement strategies used in MOVING ON can be incorporated in any study targeting OEs as a mediator of exercise or collecting exercise data with an accelerometer.